Homeless Networks in Downtown Madison, Wisconsin - Bukas, Mike; Pruzinsky, Alex; Pasqualetto, Christi (My University, 2010)
Many know that Madison, Wisconsin is a homeless-friendly city, but the question remains: does Madison have adequate resources to support its homeless community? Our research focuses specifically on the food and shelter needs of the homeless in downtown Madison. We interviewed homeless individuals to find out what their true needs are and interviewed resource providers to understand what services and resources are available. Our analysis indicates that food resources are nearly sufficient, but shelter for the homeless in downtown Madison is in need of improvement.
Includes Map, Appendix, Bibliography.
Keywords: Madison, WI; Homeless